Pengaruh Perceived Organizational Support, Servant Leadership, dan Dukungan Rekan Kerja terhadap Kepuasan Kerja Karyawan di CV Sumber Baru Niaga Yogyakarta - Ramadhon, Syahrul Adji; Kurniawan, Ignatius Soni; Septyarini, Epsilandri (Lembaga Penelitian Universitas YARSI, 2025)
Human quality resources and effective leadership are crucial in achieving optimal job satisfaction, which in turn enhances organizational performance. This study examines the influence of perceived organizational support, servant leadership, and coworker support on employee job satisfaction at CV Sumber Baru Niaga Yogyakarta. The purpose of this research is to analyze the influence of these three factors, both individually and simultaneously, on job satisfaction. A quantitative approach was applied by conducting a survey involving 98 employees. Data was collected through questionnaires and analyzed using multiple linear regression. The results indicate that perceived organizational support, servant leadership, and coworker support all have a positive effect on employee job satisfaction. Among the three variables, perceived organizational support has the most significant impact. The findings highlight the importance of a supportive organizational environment, effective leadership, and positive coworker relationships in improving job satisfaction. This study contributes to a better understanding of the factors that shape a productive and satisfying work environment, and offers practical implications for human resource management strategies, particularly in enhancing leadership and organizational support to foster a more supportive and enjoyable workplace culture.